Śrī Mahārāja Sayājīrāva Gāyakavāḍa, tisare, yāñcẽ caritra - Āpaṭe, Dājī Nāgeśa, b. 1888 (SAMP early 20th-century Indian books project ;, 1936)
Biography of Sayaji Rao Gaekwar III, Maharaja of Baroda, 1863-1939.